Sejarah Berdirinya Penyiaran Radio di Banyuwangi - Wulandari, Nuryuana Dwi (Universitas Indraprasta PGRI, 2023)
The development of radio broadcasting in Banyuwangi experienced unstable dynamics, even radio broadcasting in Banyuwangi experienced a vacuum. This research aims to find out 1) the history of the development of radio broadcasting in Banyuwangi; 2) how to maintain existence in the digital era. In this research, researchers used qualitative methods. The results of this research are 1) the history of radio development in Banyuwangi began with the birth of amateur radio stations called RADAM in 1966 with short wafe (SW) waves, in 1967-1970 there was control and they turned into radio with official broadcasts. with various conditions, the only amateur radio stations that have turned into official broadcasts are Mandala and RKPD radio which have now turned into Blambangan FM radio which has passed, 2) along with increasingly rapid technological developments and entering the era of digitalization, the existence of radio has begun to decline, Due to developments in technology, practitioners and radio station owners must be observant and more innovative in maintaining their existence, one of which is by keeping up with the times with applications in the digital era.Keywords: History, Broadcasting, Radio, Banyuwangi.